TINJAUAN HUKUM TERHADAP PELAKSANAAN PERJANJIAN PINJAMAN KPRI PRASOJO DIKBUD SUKOHARJO - Cahya Fitra Gemilang; Putri Maha Dewi; Desi Syamsiah (Bajang Institute, 2024)
This research was conducted at KPRI Prasojo Dikbud Sukoharjo in connection with the legal review of the implementation of loan agreements. The problems raised are how to implement the loan agreement and the obstacles faced in implementing the loan agreement and how to overcome the obstacles. The research method uses an empirical juridical approach with data collection methods through library data and interviews or interviews and literature studies. Then the data is presented in the form of a description of information regarding the implementation of cooperative principles and obstacles in loan agreements at KPRI Prasojo Dikbud Sukoharjo. The data obtained will be analyzed normatively qualitatively. The research results obtained from the implementation of loan agreements at KPRI Prasojo Dikbud Sukoharjo by means of cooperative members only submitting collateral in accordance with the specified goods. Then the Savings and Loans Cooperative conducted a survey of cooperative members and approved the loan application that had been submitted. Settlement of disputes if members of the cooperative are in default, then the management of KPRI Prasojo Dikbud Sukoharjo will come to the members of the cooperative and ask about the problem of why the cooperative members are unable to pay their loans. The method used is persuasive and friendly, namely by providing concessions in repayment of loans rather than using the settlement method stated in the deed of agreement. The legal review of the implementation of loan agreements at KPRI Prasojo Dikbud Sukoharjo is regulated in the Civil Code Article 1754, Article 1313, Article 1320 of the Civil Code and in Law of the Republic of Indonesia no. 25 of 1992 concerning Cooperatives and Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 14/Per/M.KUKM/XII/2009.